The view of society held by the prophets of the C 8th and C 7th B.C.E.: its social sources and implications - Oved, Aharon (Department of Religious Studies, 2025)
One of the well-known names for the prophets of the 8th century B.C.E. onwards is the “Writing Prophets”. (There are additional names for this group of prophets, "The Prophets of the Book", "Classical Prophets,” and in the Scandinavian School they are called “The Reforming Prophets””. Their emergence coincided with the appearance of Amos, -who was the first of the "writing prophets" and this phenomenon lasted for approximately 300 years. (For the social-historical background to their emergence, see Chapter 3).